Influence of the frontal joint of the bitumen sheet on the final strength of the joint - Plachý Jan (MATEC Web of Conferences, 2018)
This article focuses on the frequently discussed topic how to make the frontal joints of bitumen sheets with coarse-grained surface coating. Bitumen sheets have a spill in the place of these joints. Insufficient strength of the frontal joint is one of the possible faults in waterproofing using bitumen sheets. The paper compares different ways of performing these joints in terms of force stress based on surface treatment. Surface treatment is possible by immersing the sprinkle, scraping it into the bitumen sheet mass, or simply heating the surface and leaving it unpainted.